PENGARUH PERPUTARAN MODAL KERJA, PERPUTARAN PIUTANG DAN PERPUTARAN KAS TERHADAP PROFITABILITAS PERUSAHAAN (Survei pada Perusahaan Property dan Real Estate yang Terdaftar di Bursa Efek Indonesia Periode 2012-2014) - Dewi Saptantinah Puji Astuti, Tri Handayani, Djoko Kristianto & (Universitas Slamet Riyadi, 2016)
This research aims to analyse the effect of working capital turnover, turnover receivable, and cash turnover on profitability. This research uses purposive sampling method and obtain a sample of 38 property and real estate companies listed on The Indonesia Stock Exchange in the year of 2011-2014. The analysis method of this research that used was multiple regressions. The result showed that (1) working capital turnover has negative and not significant influence on profitability, (2) turnover receivable has positive and significant influence on profitability, (3) cash turnover has negative and not significant influence on profitability.Keywords: working capital turnover, turnover receivable, cash turnover, profitability.